2012
DOI: 10.1111/j.1439-0507.2012.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring trough voriconazole plasma concentrations in haematological patients: real life multicentre experience

Abstract: The objective of this retrospective study was to evaluate results from voriconazole therapeutic drug monitoring (TDM) in haematological patients in routine clinical practice. Between 2005 and 2010, 1228 blood samples were obtained from 264 haematological patients (median 3 samples/patient; range 1-27) receiving voriconazole for targeted/preemptive treatment of invasive aspergillosis (IA) (46.3% of samples), empirical therapy (12.9%) or prophylaxis (40.8%). A high-pressure liquid chromatography assay was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 33 publications
2
48
1
Order By: Relevance
“…However, the effect of PPIs, especially pantoprazole on the VRC C min , is far from fully under- stood since clinical studies investigating VRC pharmacokinetics have demonstrated either increased (3) or decreased (6, 41) VRC C min in patients treated with pantoprazole compared to those in untreated PPI patients. Since it is well known that PPIs competitively inhibit CYP2C19 (3,7,40), taken together, these results suggest that PPI treatment significantly contributes to the variability of VRC C min .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, the effect of PPIs, especially pantoprazole on the VRC C min , is far from fully under- stood since clinical studies investigating VRC pharmacokinetics have demonstrated either increased (3) or decreased (6, 41) VRC C min in patients treated with pantoprazole compared to those in untreated PPI patients. Since it is well known that PPIs competitively inhibit CYP2C19 (3,7,40), taken together, these results suggest that PPI treatment significantly contributes to the variability of VRC C min .…”
Section: Discussionmentioning
confidence: 56%
“…Thus, a therapeutic target of between 1 and 4 to 6 mg/liter for VRC C min has recently been proposed by the British Society for Medical Mycology (5). However, the VRC C min is frequently below this efficacy threshold in patients suffering from hematologic malignancies (6,7), notably in AHSCT patients (8).…”
mentioning
confidence: 99%
“…The Japanese practice guidelines for therapeutic drug monitoring (TDM) of voriconazole also recommend a target trough level of 1 to 2 g/ml in terms of clinical efficacy, and in patients with a trough level of Ͼ4 to 5 g/ml, elevated liver function test results potentially attributable to voriconazole should be considered (32). On the other hand, 2 recently published retrospective analyses of large-scale voriconazole TDM data from real-world clinical settings showed no associations between the voriconazole concentrations and clinical outcomes or treatmentrelated toxicity (33,34). An analysis of data from a recent phase 3 study in adult patients with IA also did not establish positive associations between the voriconazole concentrations and clinical outcomes or treatment-related toxicity when voriconazole was administered as a monotherapy (21).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has reported mixed results concerning the association of voriconazole therapeutic drug monitoring. Park et al demonstrated that therapeutic drug monitoring reduces drug discontinuation due to adverse events and improves treatment response [28]; while Racil et al failed to establish improved outcomes with measured voriconazole concentrations [29]. The true magnitude of the utility of a standardized protocol for monitoring serum concentrations of nonweight based dosing for voriconazole as primary antifungal prophylaxis has yet to occur in a prospective, randomized trial and remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The true magnitude of the utility of a standardized protocol for monitoring serum concentrations of nonweight based dosing for voriconazole as primary antifungal prophylaxis has yet to occur in a prospective, randomized trial and remains controversial. Notwithstanding the controversy of the therapeutic value of a serum voriconazole trough concentration of >1.0 and >2.0 mg/ml in the setting of voriconazole prophylaxis, [29]. The particular vulnerability of leukemia patients undergoing chemotherapy favors therapeutic drug monitoring to ensure adequate drug absorption.…”
Section: Discussionmentioning
confidence: 99%